The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1063/1.4993603
|View full text |Cite
|
Sign up to set email alerts
|

Striations in electronegative capacitively coupled radio-frequency plasmas: Effects of the pressure, voltage, and electrode gap

Abstract: Capacitively coupled radio-frequency (CCRF) CF 4 plasmas have been found to exhibit a self-organized striated structure at operating conditions, where the plasma is strongly electronegative and the ion-ion plasma in the bulk region (largely composed of CF 3 + and F − ions)resonates with the excitation frequency. In this work we explore the effects of the gas pressure, the

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 66 publications
5
42
0
1
Order By: Relevance
“…The formation of such striations was already reported in direct current (DC) glow discharges. 24,[26][27][28] For RF capacitive coupled discharges, striations have also been also observed, in electronegative gases 25 and in argon, when plasma is created between two wires wrapped around a long dielectric tube, over a certain range of frequencies and gas pressures. 29,30 The non-linear dependence of the ionization rate on the electron density is shown to be the main underlying mechanism of the striation phenomena.…”
Section: A First Characterization (Reactor A)mentioning
confidence: 99%
“…The formation of such striations was already reported in direct current (DC) glow discharges. 24,[26][27][28] For RF capacitive coupled discharges, striations have also been also observed, in electronegative gases 25 and in argon, when plasma is created between two wires wrapped around a long dielectric tube, over a certain range of frequencies and gas pressures. 29,30 The non-linear dependence of the ionization rate on the electron density is shown to be the main underlying mechanism of the striation phenomena.…”
Section: A First Characterization (Reactor A)mentioning
confidence: 99%
“…The plasma polymerization involves plasmas of complex organic vapors, which have a larger range of species including radicals, ionic oligomers and fragmented neutrals [10,11]. For this purpose, two different gases (argon and oxygen) are used and compared for an electrode separation of 22cm at a constant gas pressure of 100mTorr.…”
Section: Depositing Monomersmentioning
confidence: 99%
“…Besides, in their latest research they found that the transition could also appear by adjusting the voltage amplitude, gas pressure or electrode gap [21]. However, in all of the related investigations of STR mode, the effect of secondary electron emission on discharges was not taken into account so far, neither was the transition of the electron heating mode caused by it.…”
Section: Introductionmentioning
confidence: 99%